A reciprocal effects model of the temporal ordering of motivation and burnout among youth table tennis players in intensive training settings - Martinent, G.; Decret, J.-C.; Guillet-Descas, E.; Isoard-Gautheur, S. (Journal of Sports Sciences, 2014)
Using self-determination theory (SDT) (Deci, E.L., & Ryan, R.M. (1985). Intrinsic motivation and self-determination in human behavior. New York, NY: Plenum) as the theoretical framework, we conducted a longitudinal investigation of the temporal ordering between motivation and burnout among youth athletes in intensive training setting. Data were collected from 145 table tennis players in intensive training centres at three time points during a 2-month period characterised by a simultaneous increase in social, physical and psychological demands for these athletes. Structural equation modelling of cross-lagged panel models was used to test the hypotheses. Results showed significant paths leading from athlete burnout - especially sport devaluation and reduced sense of accomplishment - at time 1 to amotivation, intrinsic and extrinsic motivations at times 2 and 3. Only two significant paths leading from motivation (introjected regulation at time 1) to burnout (emotional/physical exhaustion at time 2 and reduced sense of accomplishment at time 3) were identified. Overall, our results suggest that athlete burnout predicts motivation over time but motivation did not predict athlete burnout over time. Results are discussed in terms of current research findings on SDT.